2018
DOI: 10.1042/bsr20181301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism by which Apis cerana cerana MKK6 (AccMKK6)-mediated MAPK cascades regulate the oxidative stress response

Abstract: Mitogen-activated protein kinase kinases (MKKs) are important components of the MAPK signaling pathways, which play a key role in responding to stress and inflammatory stimuli. Here, a new MKK gene, AccMKK6, was identified and functionally analyzed in Apis cerana cerana. Real-time quantitative PCR (qPCR) and Western blot analysis demonstrated that the AccMKK6 expression level was up-regulated by several environmental stresses. Moreover, the knockdown of AccMKK6 by RNA interference technology altered the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…MPK1 and MPK3 are critical components of MAP kinase signaling and their expressions were related to oxidative stress [28, 29]. Studies have shown that oxidative stress may be regulated by MAPK pathway [55, 56, 57]. In our study, MPK1 and MPK3 increased significantly at 0.8 mg/mL koumine and suggested that koumine may involve oxidative stress through the MAPK pathway.…”
Section: Discussionsupporting
confidence: 62%
“…MPK1 and MPK3 are critical components of MAP kinase signaling and their expressions were related to oxidative stress [28, 29]. Studies have shown that oxidative stress may be regulated by MAPK pathway [55, 56, 57]. In our study, MPK1 and MPK3 increased significantly at 0.8 mg/mL koumine and suggested that koumine may involve oxidative stress through the MAPK pathway.…”
Section: Discussionsupporting
confidence: 62%
“…Previous reports have suggested that when AccGSTO2 is knocked down, most antioxidant-related gene expression is reduced (Zhang et al, 2016). Wang reported that AccSOD1, AccSOD2, AccGSTS4, AccCYP4G11, AccGSTO2, and AccGSTD was downregulated when AccMKK6 was knocked down (Wang et al, 2018b). To further investigate the gene function of AccUGT2B20-like and the relationship between AccUGT2B20-like and oxidation-related genes, AccUGT2B20like gene was silenced.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA for first-strand complementary DNA (cDNA) synthesis was extracted from experimental honeybees using the method described by Wang (Wang et al, 2018b). RNA was reverse transcribed into cDNA using 5 Ɨ All-In-One RT MasterMix with the AccuRT Genomic DNA Removal Kit (Applied Biological Materials Inc., Richmond, British Columbia, Canada), which facilitated the elimination of contaminating genomic DNA from RNA.…”
Section: Rna Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides cause the accumulation of reactive oxygen species (ROS) in insects (Wang et al ., 2016), leading to an imbalance between antioxidant defenses and ROS production. To reduce the impact of environmental stresses, insects have evolved a range of defense mechanisms (Wang et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%